2017
DOI: 10.1007/s00256-017-2738-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic changes after steroid injection in carpal tunnel syndrome

Abstract: Ultrasound is useful in follow-up examinations of CTS. Significant ultrasound findings after steroid injections in CTS include decreased swelling of the median nerve, decreased bowing of the flexor retinaculum and increased mobility of the median nerve. All of them significantly correlate with clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…found decreased median nerve CSA (from 13.76 to 11.77 mm 2 ) at the CSA‐I in 13 patients (13 wrists) 4 weeks after a single injection of 20 mg triamcinolone. In a recent study of 18 patients (27 wrists) with CTS, Lee et al . found decreased median nerve CSA in the proximal carpal tunnel (from 10.51 to 6.60 mm 2 ) 8 weeks after a single injection of 40 mg triamcinolone.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…found decreased median nerve CSA (from 13.76 to 11.77 mm 2 ) at the CSA‐I in 13 patients (13 wrists) 4 weeks after a single injection of 20 mg triamcinolone. In a recent study of 18 patients (27 wrists) with CTS, Lee et al . found decreased median nerve CSA in the proximal carpal tunnel (from 10.51 to 6.60 mm 2 ) 8 weeks after a single injection of 40 mg triamcinolone.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the well‐established effectiveness of steroid injections for CTS, the extent to which sonographic measurements change after local steroid injection is not well understood. Only a few studies have evaluated structural changes in the median nerve after local steroid injection, and the evidence is insufficient to conclude that injections reduce median nerve CSA . Some of these studies were limited by their small samples, and some have analyzed 2 hands from the same patient, which raises potential statistical bias caused by including both between‐subject and within‐subject data.…”
mentioning
confidence: 99%
“…Ultrasound provides clear anatomic landmarks for steroids injections as part of the treatment for entrapment neuropathies; 120 in addition, it can be used to determine the clinical response to treatment. Lee et al found a significant reduction in the median nerve CSA starting 1-week post injection for CTS; changes in ultrasound parameters correlated with patient-reported improvement in pain scores 121 …”
Section: Practical Uses Of Nerve Ultrasoundmentioning
confidence: 97%
“…Lee et al found a significant reduction in the median nerve CSA starting 1-week post injection for CTS; changes in ultrasound parameters correlated with patient-reported improvement in pain scores. 121…”
Section: Injections For Entrapment Neuropathiesmentioning
confidence: 99%
“…Schrier et al showed the association between median nerve mobility and symptom severity at 3 months post-surgery [ 5 ]. Another study found significant negative correlation between the transverse sliding distance of median nerve and pain score after steroid intervention [ 28 ]. These results allowed us to monitor therapeutic effect not only with subjective pain score, but also nerve mobility to provide further morphological evidence after injection.…”
Section: Discussionmentioning
confidence: 99%